Flavonoids from the leaves and twigs of Knema elegans. (February 2020) - Lu, Zhao; Wu, Wen-Chao; Wang, Mei; Zhang, Jia-Qian; Chen, Ye-Gao; Zhan, Rui; Shao, Li-Dong
Abstract: Knema elegans, a tropical evergreen plant, belongs to Myristicaceae family. Phytochemical investigation on the leaves and twigs of K. elegans led to the isolation and identification of two new flavonoids knemavones A and B (1 and 2 ), along with fifteen known analogues (3 –17 ). These compounds belong to four subtypes of flavonoids, including chalcones, flavanes, flavones, and isoflavones. The structures of 1 and 2 were elucidated by means of spectroscopic techniques, including HRESIMS, 1D, and 2D NMR experiments. Compounds 3 –17 are isolated from the title plant for the first time. Moreover, the new chalcones 1 and 2 could serve as chemotaxonomic markers of K. elegans . Graphical abstract: Image 1 Highlights: Knema elegans is investigated on its chemical components. 17 compounds were isolated, including two new ones. Knemavones A-B (1 –2 ) are new chalcones and could be markers to distinguish K. elegans.